Reading Representations of Black Women in the Films Hidden Figures, Harriet, and The Best of Enemies, through the Views of Bell Hooks and Stuart Hall - Gül Yaşartürk (Connectist Istanbul University Journal of Communication Sciences)
Starting with D.W. Griffith’s film The Birth of a Nation (1915), black women representations in Hollywood films have been confined to the stereotypes of slavery and that of the Civil War period. While black male characters’ subject position allows identification, their female counterparts are often represented by repetitive stereotypes that lack variety. The study analyzed the films Hidden Figures (Theodore Melfi, 2016), Harriet (Kasi Lemmons, 2019), and The Best of Enemies (Robin Bissel, 2019) to understand such representative problems and question the continuity of established stereotypes in relation to black female characters and their subject position. The aforementioned films of the post-2010 mainstream Hollywood cinema depict the lives of black female figures fighting for black women’s rights, along with their experiences and real events. They were examined using the representational approach that Stuart Hall established through the concepts of “construction of difference” and “stereotyping,” as well as Bell Hooks’ views in The Oppositional Gaze: Black Female Spectators about the absence of black women who have a desire and an active mind as a subject in cinema. The paper also discusses whether the films resort to stereotyping in order to naturalize and maintain the difference in these representations and argues that all three films suggest that racial difference is a constructed and unfixed content, and that the films, except The Best of Enemies, question black women stereotypes, establishing a perspective and mechanism, that allows the audience to identify with these female characters.